Development of a laccase biosensor for determination of Phenolic micropollutants in surface waters - Souza Gil, Eric de; Rezende, Stefani Garcia; Júnior, Eli José Miranda Ribeiro; Barcelos, Hernane Toledo; Scalize, Paulo Sérgio; Santiago, Mariangela Fontes; Quintino, Michelle Pereira; Somerset, Vernon Sydwill (Univerzita Pardubice, 2014)
Laccase is a poliphenoloxidase enzyme that catalyzes the oxidation of phenolic compounds in the corresponding quinones. The current obtained in this redox process can be used for quantitative analysis. In this work, a carbon paste biosensor modified gluteraldehyde functionalized silica and an enzymatic extract of the Pycnoporus sanguineus fungi as a lacase source is proposed for phenol determination. The effect of carbon paste and electrolyte composition, pH from 3.0 to 8.0, start potential from 0.55 to 0.25 mV, scan rate from 5 to 25 mV s-1 and potential pulse amplitude from 10 to 60 mV on the differential pulse voltammetric response was investigated. A linear correlation of r² = 0.9946 was obtained for the phenol content (catechol) in the concentration range from 50 to 500 nmol L-1, with a detection limit of 30 nmol L-1. This biosensor was used for the determination of different kinds of phenolic compounds, presenting a better response for catechol.
Keywords: biosensor; laccase; phenolic micropollutants; catechol; Pycnoporus sanguineus fungi; functionalised silica